Epigenetic scars of CD8+ T cell exhaustion persist after cure of chronic infection in humans - Yates, Kathleen B.; Tonnerre, Pierre; Martin, Genevieve E.; Gerdemann, Ulrike; Al Abosy, Rose; Comstock, Dawn E.; Weiss, Sarah A.; Wolski, David; Tully, Damien C.; Chung, Raymond T.; Allen, Todd M.; Kim, Arthur Y.; et al. (Nature immunology, 2021)
T cell exhaustion is an induced state of dysfunction that arises in response to chronic infection and cancer. Exhausted CD8 + T cells acquire a distinct epigenetic state, but it is not known whether that chromatin landscape is fixed or plastic following the resolution of a chronic infection. Here we show that the epigenetic state of exhaustion is largely irreversible, even after curative therapy. Analysis of chromatin accessibility in HCV- and HIV-specific responses identifies a core epigenetic program of exhaustion in CD8 + T cells, which undergoes only limited remodeling before and after resolution of infection. Moreover, canonical features of exhaustion, including super-enhancers near the genes TOX and HIF1A , remain ‘epigenetically scarred.’ T cell exhaustion is therefore a conserved epigenetic state that becomes fixed and persists independent of chronic antigen stimulation and inflammation. Therapeutic efforts to reverse T cell exhaustion may require new approaches that increase the epigenetic plasticity of exhausted T cells. The degree of plasticity in the epigenetic landscape of exhausted T cells has been unclear. Sen and colleagues find that exhausted CD8 + T cells demonstrate a stable core epigenetic exhaustion signature that persists independent of inflammation or viral antigen.